Molecular and phenotypic analyses of yield components QTLs in IR64 backcross progenies and popular high yielding rice varieties of India - Mohapatra, S; Pandit, E; Mohanty, S P; Barik, S R; Pawar, S; Nayak, D K; Subudhi, H N; Das, Lipi; Pradhan, S K (ORYZA-An International Journal of Rice, 2018)
The projected rice demand for the increasing population across the globe is going to be very tough beyond 2040. The option of increasing yield potential of rice varieties need to be accelerated. Yield potential improvement of popular variety IR64 was taken up by introducing yield component QTLs Gn1a, Gw2, gw5, OsSPL14 and SCM2. The backcross derived lines at BC2F3 generation and popular varieties showed presence of QTLs Gn1a, Gw2, gw5, OsSPL14 and SCM2. Expected phenotypic effects were also observed in the derived lines and popular varieties. Seven derived lines were observed to possess all five yield component QTLs. Thesegenotypes may serve as useful donors for improvement of yield potential in rice.